Mediating Effect of Satisfaction on the Relationship between Teamwork and Employees Engagement in Malaysian Airlines Sector in Malaysia - Burhanuddin, Mohd Nazrin; Osman, Zahir; Raju, Valliappan (International Journal of Economics, Business and Management Studies, 2020)
The model employs Partial Least Square (PLS) procedure on data that being collected via a survey that yielded 226 usable questionnaires. The goal of this study is to look into the indirect effect of employees’ satisfaction, teamwork, and employees’ engagement relationship in Malaysian airline companies in Malaysia. To analyse the causal relationships amongst employees’ satisfaction, teamwork, and employees’ engagement, the Structural Equation Model (SEM) was implemented. The results showed that employees’ satisfaction and teamwork enhance employees’ engagement in Malaysian airline companies in Malaysia. It is essential to do the research using an experimental design by using longitudinal data in Malaysian airline companies by means of vigorous measures. The findings recommend that the airlines' companies should put emphasis on employees’ satisfaction, and working environment to ensure the advantageous increase in airways employees’ engagement at their workplace. This research is one of the original recognized efforts to use employees’ satisfaction, and working environment to study employees’ engagement in the airline's sector in Malaysia by using Partial Least Square (PLS) procedure.